Mezinárodní migrace v ČR - Dvořáková, Martina; Seidenglanz, Daniel, 1977-; Masarykova univerzita. Geografický ústav (2006)
Předkládaná bakalářská práce se zabývá zhodnocením mezinárodních migrací v České republice po roce 1989 v souvislosti s Evropskou unií. Vedle analýzy faktorů ovlivňující migraci v poslední době je věnována pozornost současnému a budoucímu vývoji migrace na našem území. Významná část práce popisuje problematiku migračním trendům mezi EU a námi, zkoumá rozdíly v evidenci migrace a její interpretaci.
The present Bachelor thesis is an assessment of the migration rate in the Czech Republic following the year 1989 and the Czech Republics becoming a member of the European Union. Along with a presentation of the factors that have been lately influencing migration, the thesis concentrates on the present and anticipated evolution of migration on our territory. An important part of the thesis describes the problematic nature of the migration flows between the Czech Republic and the European Union, explores the sources and the differences in the way migration is recorded and interpreted.
Vedoucí práce: Daniel Seidenglanz.
Bakalářská práce (Bc.)--Masarykova univerzita, Přírodovědecká fakulta, 2006.
Keywords: emigrace a imigrace; geografie obyvatelstva; migrace obyvatelstva; migrační politika; obyvatelstvo; emigration and immigration; human geography; migration policy; migration; population; Česko; země Evropské unie; Czechia; European Union countries; bakalářské práce; bachelor's theses